2001
DOI: 10.21000/jasmr01010399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biosolids Loading Rate and Sawdust Additions on Row Crop Yield and Nitrate Leaching Potentials in Virginia Sand and Gravel Mine Reclamation

Abstract: The USEPA 503 biosolids utilization rules recognize the need for higher than agronomic rate applications to mined lands under the assumption that N0 3-N contamination of groundwater will not be significant. We evaluated a range of biosolids loading rates (Ix to 7x agronomic rate of 14 Mg ha• 1) with and without added sawdust (to adjust the applied C:N ratio to approximately 20:1) on a reclaimed gravel mined soil and an undisturbed prime farmland soil for three growing seasons. The two experimental blocks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 1 publication
3
23
1
Order By: Relevance
“…Buffer strips measured I m between replications and 0.5 meter within replications. Zero tension lysimeters were placed 45 cm deep in the center of 15 of the plots (3 replications); their design is described in our companion paper (Daniels et al, 2001). Four different ratios of sawdust to biosolids (S:B) were chosen as amendments, along with a fertilized control.…”
Section: Methodsmentioning
confidence: 99%
“…Buffer strips measured I m between replications and 0.5 meter within replications. Zero tension lysimeters were placed 45 cm deep in the center of 15 of the plots (3 replications); their design is described in our companion paper (Daniels et al, 2001). Four different ratios of sawdust to biosolids (S:B) were chosen as amendments, along with a fertilized control.…”
Section: Methodsmentioning
confidence: 99%
“…Daniels et al (2001) reported the depth of initial organic-mineral horizons in sandy soils of sand-cast mining in Florida (USA) from 0.5 -5 cm after 10 years.…”
Section: Pietrzykowski and W Krzaklewskimentioning
confidence: 99%
“…As is true in many contemporary environmental problems, the rehabilitation of a drastically disturbed terrestrial system, such as lands mined for coal and minerals, requires site-specific knowledge to ensure the reclamation strategies chosen will be sustainable [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In central Europe, a large proportion of post-mining landscapes are reclaimed to forest.…”
Section: Introductionmentioning
confidence: 99%